Effects of Cognitive, Motor, and Karate Training on Cognitive Functioning and Emotional Well-Being of Elderly People - Jansen, Petra; Dahmen-Zimmer, Katharina (Frontiers in Psychology, 2012)
The present study investigated the influence of cognitive, motor, and Karate (accordingly the guidelines of the German-Karate-Federation, DKV) training on the cognitive functioning and mental state of older people between 67 and 93 years of age. The three training groups consisted of 12 elderly participants; the waiting control group included 9 participants. Before the training, participants were evaluated with cognitive measurements (cognitive speed: number connection test, number symbol test; memory performance: digit-span test, blocking-tapping test, figure test) and a measurement of emotional well-being. After this pre-testing they participated the specific training in on average 16 one-hour training sessions. The cognitive training exercised inductive thinking ability, the motor training worked on easy stretching and mobilization techniques, and the Karate training taught tasks of self-defense, partner training and Katas. After 16 training sessions all tests were applied again. The results show no significant difference in cognitive improvement dependent on group between the three training conditions. However a significant improvement was found in the emotional mental state measurement for the Karate group compared to the waiting control group. This result suggests that the high involvement in Karate leads to a feeling of self-worth and that even in elderly people integration of new sports helps to improve quality of life.